Rice Breeding for High Grain Yield under Drought: A Strategic Solution to a Complex Problem - Shalabh Dixit; Anshuman Singh; Arvind Kumar (International Journal of Agronomy)
Drought is one of the major abiotic stresses that affect rice production in rainfed areas. Recent trends in climate change have predicted a further increase in drought intensity, making the development of new drought-tolerant rice cultivars critical to sustain rice production in this ecosystem. The use of grain yield as a selection criterion at the International Rice Research Institute (IRRI), through proper population development and precise phenotyping techniques, has allowed the development of several high-yielding rice cultivars that have been released in major rainfed rice-growing areas. This strategy has also allowed the identification of several major quantitative trait loci (QTLs) that show large effects under drought across environments and genetic backgrounds. These QTLs are being pyramided together to develop drought-tolerant versions of popular drought-susceptible varieties. The near-isogenic lines (NILs) developed can replace the popular, high-yielding but drought-susceptible varieties in rainfed areas prone to drought. Additionally, these NILs serve as suitable genetic material for the study of molecular and physiological mechanisms underlying these QTLs. This may provide a better understanding of plant functions responsible for high grain yield under drought and lead to the identification of new traits and genes.